Influence of rotational motion of molecules on the thermal conductivity of solid SF6, CHCl3, C6H6, and CCl4: Low-Temperature Thermodynamics and Structure - Purskii, O.I.; Zholonko, N.N.; Konstantinov, V.A. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2003)
The thermal conductivity of solid SF6, CHCI3, C6H6, and CCl4 was investigated by the linear-flow method under saturated vapor pressures in the temperature range from 80 K to the correspondingmelting temperatures and then recalculated for a constant density of the samples. The contributions of the phonon–phonon and phonon–rotation interactions to the total thermal resistance were separated using the modified method of reduced coordinates. It is shown that the phonon–rotation contribution to the thermal resistance of the crystals decreases as the rotationalmotion of the molecules attains more freedom.